Scaling strength and power for body mass differences in rugby union players - Crewther, B. T.; Kilduff, L. P.; Cook, C. J.; Cunningham, D. J.; Bunce, P. J.; Bracken, R. M.; Gaviglio, C. M. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: This study on professional rugby union players was undertaken to: 1) confirm a relationship between body mass (BM) and peak force (PF) and peak power (PP); 2) evaluate the effect of ratio and allometric scaling on these relationships; and 3) compare the PF and PP abilities of different positional groups with each approach. METHODS: Seventy-nine rugby players were assessed for PF during an isometric mid-thigh pull and/or countermovement jump PP. Athlete performance was normalized for BM using standard ratio and allometric scaling methods. The performance data from inside backs (IB), outside backs (OB), tight forwards (TF) and loose forwards (LF) were compared before and after scaling for BM. RESULTS: Significant relationships were identified between BM and the absolute expression of PF (r=0.25) and PP (r=0.44). These relationships improved with the application of ratio scaling (r=-0.53 to -0.57), but were eliminated after allometric scaling with the derived exponents (r=0.00-0.02). No positional group differences in absolute and allometrically scaled PF and PP were seen, but ratio scaled performance favoured the lighter IB and OB over the heavier TF and/or LF (PCONCLUSION:The PF and PP abilities of professional rugby union players were related to individual BM and these relationships were differentially affected by ratio (enhanced) and allometric (removed) scaling. Ratio scaled performance favoured the lighter backs over the heavier forwards, which could be explained by their specific movement patterns